Biology and Biotechnology : science, applications, and issues - Kreuzer, Helen Massey, Adrianne (ASM Press, 2005)
"Biology and Biotechnology: Science, Applications, and Issues offers an inviting exploration of biotechnology, carefully blending science, consumer applications, regulatory information, and social issues. Providing a strong basis in the fundamentals of biological science, the book focuses on the material that is needed to understand and evaluate technologies that are available to consumers. Biology and Biotechnology